Safety, Pharmacokinetics, and Antiretroviral Activity of Intravenous 9-[2-(R)-(Phosphonomethoxy)propyl]adenine, a Novel Anti-Human Immunodeficiency Virus (HIV) Therapy, in HIV-Infected Adults - Deeks, Steven G. (American Society for Microbiology, 1998)
9-[2-(R)-(Phosphonomethoxy)propyl]adenine (PMPA) is a nucleotide analogue with potent antiretroviral activity in vitro and in simian models. A randomized, double-blind, placebo-controlled, dose-escalation clinical trial of intravenous PMPA monotherapy was conducted in 20 human immunodeficiency virus (HIV)-infected adults with CD4 cell counts of ≥200 cells/mm(3) and plasma HIV RNA levels of ≥10,000 copies/ml. Two dose levels were evaluated (1 and 3 mg/kg of body weight/day). Ten subjects were enrolled at each dose level (eight randomized to receive PMPA and two randomized to receive placebo). On day 1, a single dose of PMPA or placebo was administered by intravenous infusion. Beginning on study day 8, PMPA or placebo was administered once daily for an additional 7 consecutive days. All subjects tolerated dosing without significant adverse events. Mean peak serum PMPA concentrations were 2.7 ± 0.9 and 9.1 ± 2.1 μg/ml in the 1- and 3-mg/kg cohorts, respectively. Serum concentrations declined in a biexponential fashion, with a terminal half-life of 4 to 8 h. At 3 mg/kg/day, a single infusion of PMPA resulted in a 0.4 log(10) median decline in plasma HIV RNA by study day 8. Following 7 consecutive days of study drug administration thereafter, the median changes in plasma HIV RNA from baseline were −1.1, −0.6, and 0.1 log(10) in the 3-mg/kg/day, 1-mg/kg/day, and placebo dose groups, respectively. Following the final dose in the 3-mg/kg/day cohort, the reduction in HIV RNA was sustained for 7 days before returning toward baseline. Further studies evaluating an oral prodrug of PMPA are under way.